Acute and chronic haemodynamic effects of prazosin in left ventricular failure. Issue 2 (February 1981) - Stein, L; Foster, P R; Friedman, A W; Statza, J; McHenry, P L
Abstract : We evaluated the acute and chronic effects of prazosin treatment in 11 patients with chronic congestive heart failure, NYHA functional class III and IV. Before treatment mean arterial pressure averaged 100 +/- 15 mmHg, left ventricular filling pressure 29 +/- 11 mmHg, and systemic vascular resistance 2372 +/- 1121 dynes s cm-5. Prazosin administration resulted in haemodynamic improvement in all but one patient with significant lowering of the mean arterial pressure, left ventricular filling pressure, and systemic vascular resistance. Nine patients completed a 10-week course of ambulatory treatment. Five patients remained improved while four developed significant fluid retention; two of these had transient exacerbation of congestive heart failure. This was controlled by increasing diuretic and/or prazosin treatment. After 10 weeks all nine patients had advanced to NYHA functional class II. Repeat haemodynamic measurements disclosed complete haemodynamic tolerance in one patient while three other patients showed partial tolerance with a lower cardiac output (CO) response to prazosin. The nine patients, however, still showed significant lowering of the mean arterial pressure, left ventricular filling pressure, as well as the systemic vascular resistance. Though pharmacodynamic tolerance was noted in four out of nine patients, beneficial clinical and haemodynamic effects could be demonstrated after 10 weeks of prazosin treatment in most patients. Further evaluation of the long-term effects of prazosin in chronic congestive heart failure is warranted.